Manufacturing Acetabular Liner UHMWPE using CNC Milling - W D Lestari; L Edahwati; R D Issafira; W Saputro; A K Faizin; N Adyono; T P Sari (Biomedical and Mechanical Engineering Journal (BIOMEJ), 2021)
Ultra High Molecular Weight Polyethylene (UHMWPE) is a biomedical polymer that is useful in the orthopedic field as a bearing component in artificial hip joints. In general, these polymers pair up and rub against each other with metallic biomaterials, namely 316L stainless steel, cobalt chromium (CoCr) and titanium, which can cause material wear problems. One way to increase the wear resistance of UHMWPE is through the manufacturing process. The purpose of this research is to manufacture acetabular liner products using a CNC milling machine to obtain high surface quality and dimensional accuracy. The CNC milling machine used is the type of YCM 1020 EV 20. The manufactured specimen is then measured for roughness and dimensional accuracy. Based on the measurement results, it is found that the acetabular liner specimens from the CNC milling process are still in accordance with the standard ASTM standard (F 2033-12).